Pengawasan Kedisiplinan Peserta Didik di SMA Negeri 1 Pangkalan Lampam - Ibrahim, Ibrahim; Rosnadear, Peni; Niswah, Choirun (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to understand the process of student discipline supervision at SMA Negeri 1 Pangkalan Lampam. The researcher uses a descriptive qualitative approach with a qualitative research type. The research method employed is descriptive, with data collection techniques including observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and data verification. The validity of the data in this research is tested using source triangulation, technique triangulation, and time triangulation. The analysis results indicate that the process of supervising student discipline at SMA Negeri 1 Pangkalan Lampam involves monitoring, inspection, guidance and direction, disciplinary actions, and corrective measures. The research concludes that the supervision of student discipline at SMA Negeri 1 Pangkalan Lampam is not yet optimal, particularly in the stages of guidance or direction and disciplinary actions. This is evidenced by the students' lack of awareness regarding the importance of discipline in school